The effect of exchange rate volatility on economic growth: Case of the CEE countries - Fatbardha Morina; Eglantina Hysa; Uğur Ergün; Mirela Panait; Marian Cătălin Voica (Journal of Risk and Financial Management, 2020)
The exchange rate is a key macroeconomic factor that affects international trade and the real economy of each country. The development of international trade creates conditions where volatility comes with the exchange rate. The purpose of this paper is to examine the effect of real effective exchange rate volatility on economic growth in the Central and Eastern European countries. Additionally, the effect, through three channels of influence on economic growth which vary on the measurement of exchange rate volatility, is examined. The study uses annual data for fourteen CEE countries for the period 2002-2018 to examine the nature and extends the impact of such movements on growth. The empirical findings using the fixed effects estimation for panel data reveal that the volatility of the exchange rate has a significant negative effect on real economic growth. The results appear robust with alternative measures of exchange rate volatility such as standard deviation and z-score. This paper suggests that policymakers should adopt different policies to keep the exchange rate stable in order to foster economic growth.
Keywords: 330; CEE countries; economic growth; real effective exchange rate; volatility